Assessing the environmental impact of ruminant production systems - Takahashi, Taro (Burleigh Dodds Series in Agricultural Science, 2019)
One of the most common methods to evaluate environmental footprints of farming systems is life cycle assessment (LCA). Although LCA itself is suitable for and adopted by a wide range of industries far beyond agriculture, what separates agriculture, and in particular pasture-based ruminant production systems, is the high degree of uncertainties associated with physical, chemical and biological processes that underpin production. Through a review of recent literature and a quantitative case study, this chapter explores how the practical trade-off between feasibility and scientific rigour should be addressed in the field of ruminant production systems. Finally, the chapter provides detailed guidance on where to look for further information in the field.